Project-Based Curriculum Design in the Context of 21st Century Education - Indah Pratiwi (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
21st-century education demands the development of a curriculum that is not only oriented towards mastering knowledge, but also on strengthening critical thinking, creativity, collaboration, and communication skills. One relevant approach to address these demands is the project-based curriculum. This article aims to comprehensively examine the design of a project-based curriculum in the context of 21st-century education by integrating the views of educational experts from within and outside the country as well as the latest research findings. The method used is library research by analyzing primary reference books, reputable national and international journal articles, and educational policy documents. The results of the study indicate that a project-based curriculum is able to create meaningful, contextual, and learner-centered learning, while strengthening 21st-century skills. The conclusion of this study confirms that the design of a project-based curriculum is relevant and strategic for implementation at various levels of education, with the note that it requires support from teacher readiness, infrastructure, and sustainable policies.